The Impact of Product Quality and Customer Satisfaction on Customer Loyalty of Pempek 888 Taman Kenten Palembang - Jason Augustia; Tri Djoko; Husnan Nurjuman; Dinda Permatasari (Jurnal Mantik, 2022)
This study was conducted to determine the effect of product quality (X1) and customer satisfaction (X2) on customer loyalty (Y) Pempek 888 Restaurant Taman Kenten Palembang. This study uses a descriptive qualitative method with a sample of 98 respondents and consists of 32 statements calculated using SPSS ver.25. The results showed Product Quality with a mean of 3.70 in the very good category, Customer Satisfaction with a mean of 3.72 in the very good category, and Customer Loyalty with a mean of 3.54 in the very good category. Product Quality has a low relationship with Customer Loyalty. Customer Satisfaction has a low relationship with Customer Loyalty. Product Quality (X1) has an influence on Customer Loyalty (Y) by 15.6% and the remaining 84.4% is influenced by other factors not examined in this study. Customer Satisfaction (X2) has an effect on Customer Loyalty (Y) of 12.9% and the remaining 87.1% is influenced by other factors not examined in this study. Product Quality and Customer Satisfaction together affect Customer Loyalty.